A piezoelectric photocatalytic nanofiber membrane, its preparation method and application
The piezoelectric photocatalytic nanofiber membrane prepared by electrospinning and ultraviolet etching technology solves the problems of low efficiency and poor stability of existing photocatalytic materials, achieves high efficiency in photocatalytic hydrogen evolution and mechanical stability, and improves the structural synergy and ease of preparation of photocatalytic materials.
Patent Information
- Application Number
- CN202511224100.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-08-29
AI Technical Summary
Existing photocatalytic materials suffer from low photocatalytic efficiency, poor structural synergy, and insufficient stability. Furthermore, their preparation processes are complex and costly, making it difficult to meet the needs of fields such as water treatment and energy conversion.
Cd0.3Zn0.7S particles, TiO2, and CDs were blended into a PVDF/PAN matrix by electrospinning to construct a nanocomposite structure with high specific surface area and high dispersion, thus preparing a piezoelectric photocatalytic nanofiber membrane. The interfacial properties of the nanofiber membrane were optimized by ultraviolet etching.
It significantly improves the storage and transport efficiency of photogenerated electrons, enhances the separation of photogenerated charge carriers and the catalytic efficiency of the reaction interface, and achieves improved structural stability and mechanical strength. The photocatalytic hydrogen evolution performance is increased to 4.96 times that of pure Cd0.3Zn0.7S particles.
Smart Images

Figure CN120714658B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic materials technology, specifically to a piezoelectric photocatalytic nanofiber membrane, its preparation method, and its application. Background Technology
[0002] Photocatalysis technology, with its advantages of being green, pollution-free, and directly utilizing solar energy, shows broad application prospects in fields such as water splitting for hydrogen production and degradation of organic pollutants. Cadmium sulfide (CdS), as a typical group II-VI semiconductor material, possesses a suitable bandgap structure and excellent visible light absorption performance. However, pure CdS materials suffer from defects such as high photogenerated carrier recombination rate, severe photocorrosion, and poor stability, which greatly limit its further application in the field of photocatalysis.
[0003] To address these issues, researchers have attempted to enhance the stability and catalytic activity of catalytic materials through elemental doping, heterostructure construction, and composite material design. For example, they have combined CdS with ZnS to form Cd... x Zn 1-x While S solid solutions can modulate band gap width and photocorrosion stability to some extent, their improvement in the separation efficiency of photogenerated carriers is limited, making it difficult to achieve highly efficient photocatalytic reactions. Chinese patent CN114870869A discloses a CdZnS nanorod photocatalytic material with surface defects. Although introducing surface defects increases hydrogen evolution active sites, the synergy of its structure is insufficient when used alone, failing to fully utilize the performance advantages of each component, and the overall photocatalytic performance still cannot meet practical needs. Furthermore, TiO2 is often used to construct heterojunctions to improve carrier separation efficiency; however, single TiO2-based heterojunction materials have significant shortcomings in visible light response range and photogenerated carrier migration rate, making it difficult to further improve their photocatalytic activity.
[0004] Currently, existing photocatalytic materials generally suffer from low photocatalytic efficiency, poor structural synergy, insufficient stability, and complex preparation processes with high costs, making it difficult to meet the urgent needs of water treatment and energy conversion for efficient and stable photocatalytic materials. Therefore, it is imperative to develop a nanocomposite photocatalytic membrane material with synergistic structure, stable performance, and simple preparation to solve the above technical problems. Summary of the Invention
[0005] To address the aforementioned technical problems, the present invention aims to provide a piezoelectric photocatalytic nanofiber membrane, its preparation method, and its application. This invention integrates multiple functional components synergistically into a polymer matrix via electrospinning, forming a composite nanofiber membrane with high specific surface area, high dispersibility, and excellent photoelectric properties, suitable for environmental and energy fields such as photocatalytic hydrogen production.
[0006] The above-mentioned objective of the present invention is achieved through the following technical solution:
[0007] The first aspect of this invention provides a method for preparing a piezoelectric photocatalytic nanofiber membrane, comprising the following steps:
[0008] (1) Polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN) are dissolved in a solvent to obtain a polymer solution. Titanium dioxide (TiO2) and a surfactant are added to the polymer solution to obtain a spinning solution.
[0009] (2) Place Cd 0.3 Zn 0.7 S particles are added to the spinning solution to obtain Cd. 0.3 Zn 0.7 S spinning solution; wherein, the Cd 0.3 Zn 0.7 The mass of S particles accounts for a significant portion of the total mass of polyvinylidene fluoride, polyacrylonitrile, titanium dioxide, surfactants, and Cd. 0.3 Zn 0.7 S particles account for 5-15% of the total mass;
[0010] (3) Add the carbon dot (CDs) solution to the Cd 0.3 Zn 0.7 In the S spinning solution, a composite spinning solution is obtained; wherein the concentration of carbon dots in the carbon dot solution is 0.1-10 mg / mL, and per 5-10 g Cd 0.3 Zn 0.7 Add 0.05-0.15 mL of carbon dot solution to the S spinning solution;
[0011] (4) Electrospinning is performed on the composite spinning solution to obtain the piezoelectric photocatalytic nanofiber membrane.
[0012] This invention utilizes electrospinning technology to spin Cd 0.3 Zn 0.7 Three functional materials, S particles, TiO2, and CDs, are blended in a PVDF / PAN matrix to construct a nanocomposite structure with high specific surface area and high dispersibility, resulting in a photocatalytic nanofiber membrane that combines excellent photoelectric properties and piezoelectric effects. Specifically, the nanofiber matrix formed by the blend of PVDF and PAN possesses good mechanical flexibility, strong electroactivity, and film-forming properties; CDs exhibit excellent electron storage and transport properties, visible light response characteristics, and electron acceptor function, significantly improving the storage and transport efficiency of photogenerated electrons. Their synergistic effect with the piezoelectric effect of PVDF promotes the efficient separation of photogenerated charge carriers, thereby greatly enhancing the photocatalytic performance.
[0013] Furthermore, in step (1), the mass ratio of PVDF to PAN is (3-7):(1-5). When the mass ratio is too low, the piezoelectric activity of the matrix is insufficient, and when the mass ratio is too high, the mechanical flexibility decreases.
[0014] Further, in step (1), the total concentration of PVDF and PAN in the polymer solution is 10-15 wt%.
[0015] Further, in step (1), the solvent includes an organic solvent and a co-solvent, wherein the organic solvent is selected from one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP) and dimethyl sulfoxide (DMSO), and the co-solvent is selected from one or more of acetic acid (Ac), trifluoroacetic acid (TFA), formic acid and acetone.
[0016] Preferably, the solvent is a mixed solvent of DMF and Ac, a mixed solvent of DMAc and TFA, a mixed solvent of NMP and formic acid, or a mixed solvent of DMSO and acetone.
[0017] Furthermore, the mass ratio of the organic solvent to the co-solvent is (6-9):(1-4).
[0018] Further, in step (1), the amount of TiO2 added to the polymer solution is 0.05-0.2 wt%. If the amount added is less than 0.05 wt%, there will be insufficient photocatalytic sites, and if the amount added exceeds 0.2 wt%, it will easily agglomerate and reduce dispersibility.
[0019] Furthermore, in step (1), the titanium dioxide (TiO2) added to the polymer solution is in powder form, and TiO2 serves as a piezoelectric enhancer.
[0020] Further, in step (1), the amount of surfactant added to the polymer solution is 0.1-0.3 wt%.
[0021] Further, in step (1), the surfactant is selected from one or more of hexadecyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium chloride (DTAC), octadecyltrimethylammonium bromide (STAB) and sodium dodecylbenzenesulfonate (SDBS), preferably CTAB.
[0022] Further, in step (2), the Cd 0.3 Zn 0.7 The preparation method of S particles includes the following steps: dissolving cadmium salt and zinc salt in water at a molar ratio of 3:7, adding a sulfur source to form a precursor solution, and obtaining the Cd particles after a hydrothermal reaction. 0.3 Zn 0.7 S particles.
[0023] This invention prepares three-dimensional cauliflower-shaped Cd by a solvothermal method. 0.3 Zn 0.7 S nanoparticles were uniformly embedded into a PVDF / PAN composite nanofiber matrix using electrospinning technology, successfully preparing a device-ready piezoelectric photocatalytic nanofiber membrane material with both structural integrity and flexibility. This method effectively overcomes the limitations of traditional powder catalysts, such as poor dispersibility and difficult recovery, enabling Cd... 0.3 Zn 0.7 S particles are uniformly distributed within the high specific surface area fiber membrane, significantly enhancing the material's light-harvesting ability and reaction site density, thereby improving the catalytic efficiency of the reaction interface. Furthermore, Cd... 0.3 Zn 0.7 The introduction of S particles enhances the hydrophilicity and mechanical strength of the composite nanofiber membrane, which is beneficial for wetting the reaction medium and exposing the catalytic sites, thereby improving the diffusion efficiency of reactants and the structural stability of the membrane during photocatalysis.
[0024] Furthermore, the cadmium salt includes, but is not limited to, cadmium acetate, cadmium nitrate, cadmium chloride and their hydrates, preferably cadmium acetate (Cd(Ac)2·2H2O).
[0025] Furthermore, the zinc salt includes, but is not limited to, zinc acetate, zinc nitrate, zinc chloride and their hydrates, preferably zinc acetate (Zn(Ac)2·2H2O).
[0026] Furthermore, the sulfur source includes, but is not limited to, thiourea, sodium sulfide, and thioacetamide, with thiourea being preferred.
[0027] Furthermore, the temperature of the hydrothermal reaction is 120-180 ℃. Below 120 ℃, the reaction may be incomplete, and above 180 ℃, it is easy to cause particle agglomeration.
[0028] Furthermore, the hydrothermal reaction time is 12-48 h.
[0029] Furthermore, the process after the hydrothermal reaction is completed includes centrifugation, washing, and drying steps.
[0030] Further, in step (2), the Cd 0.3 Zn 0.7 The particle size of S particles is 50-100 nm, preferably 80-100 nm.
[0031] Preferably, the Cd 0.3 Zn 0.7 The mass of S particles accounts for a significant portion of the total mass of polyvinylidene fluoride, polyacrylonitrile, titanium dioxide, surfactants, and Cd. 0.3 Zn 0.7 S particles account for 7.5-12.5% of the total mass.
[0032] Further, in step (2), the Cd in the spinning solution 0.3 Zn 0.7 When the amount of S particles added is too low, there are insufficient photocatalytic active sites; when the amount added is too high, it may lead to particle agglomeration, reduce dispersibility and affect the mechanical properties of the nanofiber membrane.
[0033] Furthermore, in step (3), every 5-10 g of Cd 0.3 Zn 0.7 Adding 0.05-0.15 mL of carbon dot solution to the S spinning solution achieves good hydrogen evolution performance within this range. Too low a carbon dot addition results in limited improvement in charge separation efficiency; too high a carbon dot addition may lead to abnormal viscosity of the spinning solution, affecting fiber forming quality.
[0034] Preferably, in step (3), every 5-10 g of Cd 0.3 Zn 0.7 Add 0.075-0.125 mL of carbon dot solution to the S spinning solution.
[0035] Furthermore, in step (3), the carbon dots in the carbon dot solution include, but are not limited to, graphene quantum dots, carbon nanodots, and carbon quantum dots.
[0036] Preferably, in step (3), the concentration of carbon dots in the carbon dot solution is 1-5 mg / mL, and the synergistic effect is not significant when the concentration is too low.
[0037] Furthermore, in step (3), the particle size of the carbon dots in the carbon dot solution is 2-5 nm.
[0038] Furthermore, in step (3), the solvent of the carbon dot solution includes, but is not limited to, water, ethanol, and N,N-dimethylformamide.
[0039] Furthermore, in step (3), the carbon dot solution can be prepared by electrolysis, hydrothermal method, microwave method or laser ablation method.
[0040] The CDs prepared by electrolysis are rich in functional groups such as hydroxyl and carboxyl groups on their surface, which form hydrogen bonds with the PVDF / PAN matrix to ensure uniform dispersion in the spinning solution. Furthermore, the electron transport path is optimized through the π-π conjugation effect, forming a synergistic effect with the matrix and improving the visible light response range and photoelectric conversion efficiency of the composite system.
[0041] Further, in step (4), the electrospinning process parameters are: voltage of 8-15 kV, liquid feed rate of 0.3-1.0 mL / h, spinneret inner diameter of 0.3-0.8 mm, receiving distance of 15-25 cm, collecting roller speed of 300-1000 r / min, temperature of 20-30 ℃, and humidity of 45-55%.
[0042] Further, in step (4), the composite spinning solution is electrospun, and the resulting composite nanofiber membrane is subjected to ultraviolet etching treatment to obtain the piezoelectric photocatalytic nanofiber membrane.
[0043] This invention utilizes ultraviolet etching technology to optimize the interfacial properties of nanofiber membranes, increase the exposure of active sites, reduce the nanoparticle encapsulation rate, further enhance the surface reactivity of nanofiber membranes, and achieve optimized catalytic performance.
[0044] Furthermore, the ultraviolet etching process uses ultraviolet light with a wavelength of 300-380 nm.
[0045] Preferably, the ultraviolet etching process uses a UV lamp with a wavelength of 365 nm.
[0046] Furthermore, the UV etching process takes 10-60 minutes. If the etching time is too short, the active sites will not be sufficiently exposed, resulting in limited improvement in catalytic performance; if the etching time is too long, it may lead to over-etching of nanoparticles, damaging the structural integrity of the nanofiber membrane.
[0047] Preferably, the ultraviolet etching process takes 30-50 minutes.
[0048] Furthermore, in step (4), the thickness of the piezoelectric photocatalytic nanofiber membrane is 100-120 μm.
[0049] The second aspect of the present invention provides a piezoelectric photocatalytic nanofiber membrane prepared by the preparation method described in the first aspect.
[0050] The piezoelectric photocatalytic nanofiber membrane provided by this invention has a stable structure, is easy to recycle, and has good application prospects.
[0051] The third aspect of this invention provides an application of the piezoelectric photocatalytic nanofiber membrane described in the second aspect in photocatalytic hydrogen evolution.
[0052] The piezoelectric nanocomposite fiber membrane constructed in this invention can achieve photo / piezoelectric synergistic catalysis, which can improve the surface charge mobility under the condition of no external electric field, thereby promoting the improvement of photocatalytic efficiency.
[0053] The piezoelectric photocatalytic nanofiber membrane provided by this invention possesses excellent photocatalytic hydrogen evolution performance and mechanical stability. Pure Cd 0.3 Zn 0.7 The photocatalytic hydrogen evolution rate of S particles in pure water under simulated sunlight conditions was 15.6 mmol / g / h; the photocatalytic hydrogen evolution rate of the untreated composite nanofiber membrane in pure water under simulated sunlight conditions reached 49.4 mmol / g / h, which is the rate of pure Cd. 0.3 Zn 0.7 The efficiency of S particles is 3.17 times that of pure Cd; the piezoelectric photocatalytic nanofiber membrane treated with ultraviolet etching achieves a photocatalytic hydrogen evolution efficiency of up to 77.4 mmol / g / h under simulated sunlight conditions, which is higher than that of pure Cd. 0.3 Zn 0.7 4.96 times that of S particles.
[0054] The beneficial effects of this invention are:
[0055] 1. The introduction of Cd into the piezoelectric photocatalytic nanofiber membrane provided by this invention significantly improves the storage and transport efficiency of photogenerated electrons. As an electron acceptor, it can effectively capture photogenerated electrons and reduce carrier recombination. Simultaneously, the piezoelectric effect of PVDF generates a piezoelectric potential under mechanical deformation, which synergistically works with the electron transport performance of Cd to promote the directional migration and separation of photogenerated carriers. Furthermore, Cd... 0.3 Zn 0.7 S solid solution enhances visible light absorption by adjusting the band gap width, while TiO2 further optimizes charge separation efficiency with its stable photocatalytic performance and electron transport capability. The synergistic effect of multiple components achieves a systematic improvement in photocatalytic activity.
[0056] 2. This invention involves ultraviolet etching of the composite nanofiber membrane, which selectively etches the polymer matrix surface through photochemical action, increasing Cd content. 0.3 Zn 0.7 The exposure of nanoparticles such as S and TiO2 is reduced, decreasing their embedding rate in the matrix without compromising the structural integrity of the composite nanofiber membrane. This treatment not only significantly improves the specific surface area and light absorption capacity of the material, but also enhances surface reactivity by exposing catalytically active sites (such as sulfur vacancies and hydroxyl groups), providing more reaction sites for photocatalytic hydrogen evolution.
[0057] 3. In the piezoelectric photocatalytic nanofiber membrane provided by this invention, the piezoelectric properties of the PVDF matrix generate a built-in electric field under the action of external force, which promotes the separation of photogenerated carriers. This makes the hydrogen evolution efficiency of the piezoelectric photocatalytic nanofiber membrane under piezoelectric synergy reach 1.48 times that under non-piezoelectric conditions (in the photocatalytic hydrogen evolution performance test, no magnetic stirring was performed, only light treatment was performed), verifying its application potential in the field of mechanical-photocatalytic coupling.
[0058] 4. The piezoelectric photocatalytic nanofiber membrane provided by this invention has a stable structure and maintains a high hydrogen evolution efficiency in multiple rounds of photocatalytic experiments, demonstrating excellent reusability and environmental adaptability. Attached Figure Description
[0059] Figure 1 UV C prepared in Example 9 7.5 Scanning electron microscope (SEM) image of TPP-0.125CDs nanofiber membrane.
[0060] Figure 2 For Cd 0.3 Zn 0.7 The graph shows the photocatalytic hydrogen evolution rate data of S particles and nanofiber membranes prepared in Comparative Examples 1-6.
[0061] Figure 3 The graph shows the photocatalytic hydrogen evolution rate data of nanofiber membranes prepared by comparative examples 1-6 after UV etching for different times.
[0062] Figure 4 The graph shows the photocatalytic hydrogen evolution rate data of the 7.5-CTPP nanofiber membrane prepared in Comparative Example 2 and the piezoelectric photocatalytic nanofiber membranes prepared in Examples 1-5.
[0063] Figure 5 The graph shows the photocatalytic hydrogen evolution rate data of the piezoelectric photocatalytic nanofiber membranes prepared in Examples 1 and 6-11.
[0064] Figure 6 The 7.5-CTPP nanofiber membrane prepared in Comparative Example 2 and the C2000 nanofiber membrane prepared in Example 1 are compared. 7.5 Figure 1 shows the piezoelectric properties of TPP-0.125CDs nanofiber membrane; where (a) is the periodic variation of voltage, (b) is the periodic variation of current, and (c) is the periodic variation of charge. Detailed Implementation
[0065] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0066] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0067] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.
[0068] Cd in the following examples 0.3 Zn 0.7 S particles were prepared by the following method: 0.1919 g of cadmium acetate dihydrate (Cd(Ac)₂·2H₂O) and 0.3688 g of zinc acetate dihydrate (Zn(Ac)₂·2H₂O) were weighed and added to a 100 mL beaker at a molar ratio of 3:7. 60 mL of deionized water was added, and the mixture was magnetically stirred for 30 minutes at room temperature until completely dissolved. Then, 2.736 g of thiourea (CH₄N₂S) was added, and stirring continued for 30 minutes to form a mixed liquid. The above mixed liquid was transferred to a stainless steel autoclave with a polytetrafluoroethylene liner and hydrothermally reacted at 140 °C for 24 hours. After the reaction, the mixture was naturally cooled to room temperature, and the resulting mixture was removed and centrifuged (4000 r / min, 20 min). After washing several times alternately with deionized water and ethanol, the mixture was dried in a vacuum drying oven at 60 °C for 12 hours to obtain Cd particles with a particle size of 50-100 nm. 0.3 Zn 0.7 S particles.
[0069] In the following examples, the CDs solution was prepared by the following electrolytic method: Graphite rods were inserted as positive and negative electrodes into a large beaker containing ultrapure water and ultrasonically cleaned for 30 minutes to remove impurities. Subsequently, long-term electrolysis (approximately two weeks) was performed at room temperature until the system turned dark brown. The resulting liquid was filtered through filter paper and centrifuged at high speed to remove residual large graphite particles, thus obtaining a stable and dispersed CDs solution; wherein the concentration of carbon dots in the carbon dot solution was 3 mg / mL.
[0070] In the following test example, CdZnS nanorods were prepared by the following method: 8 mmol of thiourea, 3 mmol of Cd(Ac)2·2H2O and 27 mmol of Zn(Ac)2·2H2O were weighed and mixed in a 150 mL beaker, transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and hydrothermally reacted at 160 °C for 24 h. The product was washed with water, washed with alcohol, centrifuged and dried to obtain CdZnS nanorods.
[0071] Example 1
[0072] A piezoelectric photocatalytic nanofiber membrane (C 7.5 The preparation method of TPP-0.125CDs includes the following steps:
[0073] (1) Dissolve 0.525 g PVDF and 0.315 g PAN (mass ratio 5:3) in a mixed solvent of 4.928 g DMF and 1.232 g Ac (mass ratio 8:2), and stir at 60 °C for 2 h to form a uniform and transparent polymer solution. Add 0.0084 g TiO2 and 0.0187 g CTAB to the polymer solution and stir evenly to obtain TiO2 / PVDF / PAN spinning solution, abbreviated as TPP spinning solution;
[0074] (2) Put 0.0703 g Cd 0.3 Zn 0.7 S particles were added to the TPP spinning solution and stirred at room temperature for 12 h to obtain a 7.5-CTPP spinning solution (where 7.5 refers to Cd). 0.3 Zn 0.7 S particles account for a significant portion of the total solute (polyvinylidene fluoride, polyacrylonitrile, titanium dioxide, surfactants, and Cd). 0.3 Zn 0.7 S particles) 7.5% of the mass, CTPP refers to Cd 0.3 Zn 0.7 S / TiO2 / PVDF / PAN);
[0075] (3) Add 0.125 mL of CDs solution to 7.5-CTPP spinning solution to obtain C 7.5 TPP-0.125CDs composite spinning solution (where 0.125 refers to the volume of CDs solution added, in mL).
[0076] (4) A self-made electrospinning device was used to spin C 7.5 The TPP-0.125CDs composite spinning solution was electrospun under the following conditions: voltage 11.5 kV, feed rate 0.6 mL / h, spinneret inner diameter 0.5 mm, receiving distance 20 cm, collecting roller speed 550 r / min, temperature 25 ℃, and humidity 50%. After spinning, the composite nanofiber membrane was dried in a 60 ℃ oven for 6 h to obtain C 7.5 TPP-0.125CDs nanofiber membrane.
[0077] Example 2
[0078] A piezoelectric photocatalytic nanofiber membrane (C 7.5 The preparation method of TPP-0.05CDs is basically the same as that in Example 1, except that in step (3), 0.05 mL of CDs solution is added to 7.5-CTPP spinning solution.
[0079] Example 3
[0080] A piezoelectric photocatalytic nanofiber membrane (C 7.5 The preparation method of TPP-0.075CDs is basically the same as that in Example 1, except that in step (3), 0.075 mL of CDs solution is added to 7.5-CTPP spinning solution.
[0081] Example 4
[0082] A piezoelectric photocatalytic nanofiber membrane (C 7.5 The preparation method of TPP-0.1CDs is basically the same as that in Example 1, except that in step (3), 0.1 mL of CDs solution is added to 7.5-CTPP spinning solution.
[0083] Example 5
[0084] A piezoelectric photocatalytic nanofiber membrane (C 7.5 The preparation method of TPP-0.15CDs is basically the same as that in Example 1, except that in step (3), 0.15 mL of CDs solution is added to 7.5-CTPP spinning solution.
[0085] Example 6
[0086] A piezoelectric photocatalytic nanofiber membrane (UV C 7.5 The preparation method of TPP-0.125CDs is basically the same as that in Example 1, except that in step (4), C 7.5 The TPP-0.125CDs nanofiber membrane was subjected to UV etching with a 365 nm wavelength UV lamp for 10 min to activate more active sites of the embedded particles, thus obtaining UV C. 7.5 TPP-0.125CDs nanofiber membrane.
[0087] Example 7
[0088] A piezoelectric photocatalytic nanofiber membrane (UV C 7.5 The preparation method of TPP-0.125CDs is basically the same as that in Example 6, except that the UV etching time is 20 min.
[0089] Example 8
[0090] A piezoelectric photocatalytic nanofiber membrane (UV C 7.5 The preparation method of TPP-0.125CDs is basically the same as that in Example 6, except that the UV etching time is 30 min.
[0091] Example 9
[0092] A piezoelectric photocatalytic nanofiber membrane (UV C7.5 The preparation method of TPP-0.125CDs is basically the same as that in Example 6, except that the UV etching time is 40 min.
[0093] Figure 1 UV C prepared in Example 9 7.5 SEM image of TPP-0.125CDs nanofiber membrane.
[0094] Example 10
[0095] A piezoelectric photocatalytic nanofiber membrane (UV C 7.5 The preparation method of TPP-0.125CDs is basically the same as that in Example 6, except that the UV etching time is 50 min.
[0096] Example 11
[0097] A piezoelectric photocatalytic nanofiber membrane (UV C 7.5 The preparation method of TPP-0.125CDs is basically the same as that in Example 6, except that the UV etching time is 60 min.
[0098] Comparative Example 1
[0099] A method for preparing a TPP nanofiber membrane includes the following steps:
[0100] (1) Dissolve 0.525 g PVDF and 0.315 g PAN (mass ratio 5:3) in a mixed solvent of 4.928 g DMF and 1.232 g Ac (mass ratio 8:2), and stir at 60 °C for 2 h to form a uniform and transparent polymer solution. Add 0.0084 g TiO2 and 0.0187 g CTAB to the polymer solution and stir evenly to obtain TiO2 / PVDF / PAN spinning solution, abbreviated as TPP spinning solution;
[0101] (2) The TPP spinning solution was electrospun using a self-made electrospinning device under the following conditions: voltage of 11.5 kV, feed rate of 0.6 mL / h, spinneret inner diameter of 0.5 mm, receiving distance of 20 cm, collecting roller speed of 550 r / min, temperature of 25 ℃ and humidity of 50%. After spinning, the nanofiber membrane was dried in an oven at 60 ℃ for 6 h to obtain the TPP nanofiber membrane.
[0102] Comparative Example 2
[0103] A method for preparing a 7.5-CTPP nanofiber membrane includes the following steps:
[0104] (1) Dissolve 0.525 g PVDF and 0.315 g PAN (mass ratio 5:3) in a mixed solvent of 4.928 g DMF and 1.232 g Ac (mass ratio 8:2), and stir at 60 °C for 2 h to form a uniform and transparent polymer solution. Add 0.0084 g TiO2 and 0.0187 g CTAB to the polymer solution and stir evenly to obtain TiO2 / PVDF / PAN spinning solution, abbreviated as TPP spinning solution;
[0105] (2) Put 0.0703 g Cd 0.3 Zn 0.7 S particles were added to the TPP spinning solution and stirred at room temperature for 12 h to obtain a 7.5-CTPP spinning solution (where 7.5 refers to Cd). 0.3 Zn 0.7 S particles account for a significant portion of the total solute (polyvinylidene fluoride, polyacrylonitrile, titanium dioxide, surfactants, and Cd). 0.3 Zn 0.7 S particles) 7.5% of the mass, CTPP refers to Cd 0.3 Zn 0.7 S / TiO2 / PVDF / PAN);
[0106] (3) Electrospinning of 7.5-CTPP spinning solution was carried out using a self-made electrospinning device under the following conditions: voltage of 11.5 kV, liquid feed rate of 0.6 mL / h, spinneret inner diameter of 0.5 mm, receiving distance of 20 cm, collecting roller speed of 550 r / min, temperature of 25 ℃, and humidity of 50%. After spinning, the composite nanofiber membrane was dried in an oven at 60 ℃ for 6 h to obtain 7.5-CTPP nanofiber membrane.
[0107] Comparative Example 3
[0108] A method for preparing a 5-CTPP nanofiber membrane is basically the same as that for Comparative Example 2, except that in step (2), Cd... 0.3 Zn 0.7 S particles account for 5% of the total solute mass.
[0109] Comparative Example 4
[0110] A method for preparing a 10-CTPP nanofiber membrane is basically the same as that for Comparative Example 2, except that in step (2), Cd... 0.3 Zn 0.7 S particles account for 10% of the total solute mass.
[0111] Comparative Example 5
[0112] A method for preparing a 12.5-CTPP nanofiber membrane is basically the same as that for Comparative Example 2, except that in step (2), Cd... 0.3 Zn 0.7 S particles account for 12.5% of the total solute mass.
[0113] Comparative Example 6
[0114] A method for preparing a 15-CTPP nanofiber membrane is basically the same as that for Comparative Example 2, except that in step (2), Cd... 0.3 Zn 0.7 S particles account for 15% of the total solute mass.
[0115] Test Example 1
[0116] For Cd 0.3 Zn 0.7 The photocatalytic performance of S-particles (CZS), nanofiber membranes prepared in Examples 1-11 and Comparative Examples 1-6 was tested using the following methods:
[0117] Put 0.05 g Cd 0.3 Zn 0.7 S-sized particles or 1 cm 2 The nanofiber membrane was placed in a 30 mL transparent vial, and 15 mL of ultrapure water containing 0.35 M Na₂S and 0.25 M Na₂SO₃ was added. The vial was then sealed with a rubber stopper and an aluminum pressure cap. The photocatalytic hydrogen evolution experiment was conducted under visible light irradiation (420 nm ≤ incident wavelength λ ≤ 700 nm) for 5 h, with magnetic stirring (a stirring rotor was placed in the vial, and the rotor stirred at a constant speed) at 200 r / min. After irradiation, 2.5 mL of gas was drawn from the vial using a 5 mL syringe, and the hydrogen was quantitatively analyzed by gas chromatography. The photocatalytic hydrogen evolution rate was obtained by dividing the amount of hydrogen generated by the mass of the catalyst and the irradiation time (in hours).
[0118] Test results are as follows Figures 2-5 As shown, Figure 2 For Cd 0.3 Zn 0.7 The graph shows the photocatalytic hydrogen evolution rate data of S particles and nanofiber membranes prepared in Comparative Examples 1-6. Figure 2 As can be seen, the TPP nanofiber membrane does not possess photocatalytic properties; Cd 0.3 Zn 0.7 S particles exhibited certain photocatalytic activity under initial irradiation, with a hydrogen evolution rate of approximately 15.6 mmol / g / h; in comparative examples 2-6 with different Cd... 0.3 Zn 0.7Among the nanofiber membranes prepared with high S particle content, the 7.5-CTPP nanofiber membrane exhibits better photocatalytic performance, with a hydrogen evolution rate of approximately 27.1 mmol / g / h under visible light.
[0119] Figure 3 The graph shows the photocatalytic hydrogen evolution rate data of the nanofiber membranes prepared in Comparative Examples 1-6 after UV etching for different times. Figure 3 As can be seen, except for the 5-CTPP nanofiber membrane, the photocatalytic performance of other nanofiber membranes is improved after a certain period of UV etching treatment. The hydrogen evolution rate of the 7.5-CTPP nanofiber membrane under visible light can reach 33.5 mmol / g / h after UV etching treatment for 10 min, and the hydrogen evolution rate of the 10-CTPP nanofiber membrane under visible light can reach 24 mmol / g / h after UV etching treatment for 30 min.
[0120] Figure 4 The graphs show the photocatalytic hydrogen evolution rate data of the 7.5-CTPP nanofiber membrane prepared in Comparative Example 2 and the piezoelectric photocatalytic nanofiber membranes prepared in Examples 1-5. Figure 4 As can be seen from the image, the C20 prepared after adding carbon dot solution... 7.5 The TPP-0.125CDs nanofiber membrane achieved a hydrogen evolution rate of 49.4 mmol / g / h under visible light, which is 82% higher than that of the 7.5-CTPP nanofiber membrane.
[0121] Figure 5 The graph shows the photocatalytic hydrogen evolution rate data of the piezoelectric photocatalytic nanofiber membranes prepared in Examples 1 and 6-11. Figure 5 As can be seen from this, C 7.5 After UV etching for 40 min, the hydrogen evolution rate of the TPP-0.125CDs nanofiber membrane under visible light increased by 56% to 77.4 mmol / g / h, demonstrating good stability, high photoresponse, and recyclability.
[0122] In addition, for Cd 0.3 Zn 0.7 S particles, CdZnS nanorods, and the UV C prepared in Example 9 7.5 Cyclic testing of the photocatalytic performance of TPP-0.125CDs nanofiber membranes was conducted at UV C. 7.5 The TPP-0.125CDs nanofiber membrane retained over 90% of its performance after three cycles; Cd 0.3 Zn 0.7S particles exhibit poor dispersibility and low stability, with performance decreasing by more than 50% after three cycles. The method for testing the photocatalytic performance of CdZnS nanorods is as follows: after cleaning, a glass substrate is immersed in a 12 wt% polymethyl methacrylate (PMMA) solution for surface treatment, followed by immersion in a 7.5 wt% CdZnS nanorod solution to form a catalytic film. The photocatalytic performance of the film is then tested. The initial hydrogen evolution rate of the film is 15.6 mmol / g / h, but after three cycles, the efficiency decreases to 65% of the initial value, which is significantly lower than the stability and photocatalytic performance of the nanofiber membrane of this invention.
[0123] Test Example 2
[0124] The 7.5-CTPP nanofiber membrane prepared in Comparative Example 2 and the C20-C20 nanofiber membrane prepared in Example 1 were compared. 7.5 The piezoelectric properties of the TPP-0.125CDs nanofiber membrane were tested, including periodic changes in voltage, current, and charge. The test method was as follows:
[0125] Under a frequency of 3 Hz and a pressure of 10 N, the voltage, current and charge generated by a 2.5 cm × 2.5 cm nanofiber membrane were measured in a 5 s period using copper foil as a conductor.
[0126] Data analysis of the test results shows that C 7.5 TPP-0.125CDs nanofiber membranes exhibit significantly better piezoelectric effects than 7.5-CTPP nanofiber membranes, demonstrating higher voltage, stronger current, and greater charge accumulation. For example... Figure 6 As shown in (a), C 7.5 The voltage of the TPP-0.125CDs nanofiber membrane is 10.9 V, higher than that of the 7.5-CTPP nanofiber membrane (9.1 V). This indicates that the nanofiber membrane can generate a stronger built-in electric field under external mechanical stress, thereby promoting the separation of photogenerated electrons and holes. This higher piezoelectric potential helps to improve the carrier migration efficiency in the photocatalytic reaction, reduce electron-hole recombination, and further enhance photocatalytic efficiency. Figure 6 As shown in (b), in terms of current response, C 7.5 The current of the TPP-0.125CDs nanofiber membrane was 1.2 nA, significantly higher than that of the 7.5-CTPP nanofiber membrane (0.82 nA), indicating that C 7.5 TPP-0.125CDs nanofiber membranes can generate stronger piezoelectric currents under stress, which can assist in the separation and transport of photogenerated charges in photocatalysis by providing greater electrodynamic force. Figure 6 As can be seen from (c), C 7.5The charge accumulation of the TPP-0.125CDs nanofiber membrane is 5.4 μC, which is higher than that of the 7.5-CTPP nanofiber membrane (3.5 μC). This indicates that the nanofiber membrane can accumulate more charge under external force. The accumulation of charge forms a local electric field, which can further promote the effective separation of electrons and holes and maintain the high efficiency of photocatalytic reaction.
[0127] C 7.5 The TPP-0.125CDs nanofiber membrane significantly enhances the piezoelectric effect by introducing CDs. This is because the large specific surface area and abundant surface defects of CDs provide favorable surface active sites, optimize the polar environment of PVDF, promote the formation and stabilization of the β phase, and thus improve the separation and migration efficiency of photogenerated electrons. The stronger voltage response, higher current, and larger charge accumulation indicate that CDs play a crucial role in improving piezoelectric-photocatalytic performance, enabling the nanofiber membrane to exhibit stronger catalytic activity in the hydrogen evolution reaction.
[0128] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a piezoelectric photocatalytic nanofiber membrane, characterized in that, Includes the following steps: (1) Polyvinylidene fluoride and polyacrylonitrile are dissolved in a solvent to obtain a polymer solution. Titanium dioxide and a surfactant are added to the polymer solution to obtain a spinning solution. (2) Place Cd 0.3 Zn 0.7 S particles are added to the spinning solution to obtain Cd. 0.3 Zn 0.7 S spinning solution; wherein, the Cd 0.3 Zn 0.7 The mass of S particles accounts for a significant portion of the total mass of polyvinylidene fluoride, polyacrylonitrile, titanium dioxide, surfactants, and Cd. 0.3 Zn 0.7 S particles account for 5-15% of the total mass; (3) Add the carbon dot solution to the Cd 0.3 Zn 0.7 In the S spinning solution, a composite spinning solution is obtained; wherein the concentration of carbon dots in the carbon dot solution is 0.1-10 mg / mL, and per 5-10 g Cd 0.3 Zn 0.7 Add 0.05-0.15 mL of carbon dot solution to the S spinning solution; (4) Electrospinning is performed on the composite spinning solution to obtain the piezoelectric photocatalytic nanofiber membrane.
2. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of polyvinylidene fluoride to polyacrylonitrile is (3-7):(1-5); the total concentration of polyvinylidene fluoride and polyacrylonitrile in the polymer solution is 10-15 wt%.
3. The preparation method according to claim 1, characterized in that, In step (1), the solvent includes an organic solvent and a co-solvent. The organic solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide. The co-solvent is selected from one or more of acetic acid, trifluoroacetic acid, formic acid and acetone. The mass ratio of the organic solvent to the co-solvent is (6-9):(1-4).
4. The preparation method according to claim 1, characterized in that, In step (1), the amount of TiO2 added to the polymer solution is 0.05-0.2 wt%.
5. The preparation method according to claim 1, characterized in that, In step (1), the amount of surfactant added to the polymer solution is 0.1-0.3 wt%; the surfactant is selected from one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, octadecyltrimethylammonium bromide and sodium dodecylbenzenesulfonate.
6. The preparation method according to claim 1, characterized in that, In step (4), the electrospinning process parameters are as follows: voltage 8-15 kV, liquid feed rate 0.3-1.0 mL / h, spinneret inner diameter 0.3-0.8 mm, receiving distance 15-25 cm, collecting roller speed 300-1000 r / min, temperature 20-30 ℃, and humidity 45-55%.
7. The preparation method according to claim 1, characterized in that, In step (4), the composite spinning solution is electrospun, and the resulting composite nanofiber membrane is subjected to ultraviolet etching treatment to obtain the piezoelectric photocatalytic nanofiber membrane.
8. The preparation method according to claim 7, characterized in that, The ultraviolet etching process uses ultraviolet light with a wavelength of 300-380 nm; the ultraviolet etching process takes 10-60 min.
9. A piezoelectric photocatalytic nanofiber membrane prepared by the preparation method according to any one of claims 1-8.
10. The application of the piezoelectric photocatalytic nanofiber membrane according to claim 9 in photocatalytic hydrogen evolution.
Citation Information
Patent Citations
CdZnS nanorod photocatalytic material with surface defects as well as preparation method and application of CdZnS nanorod photocatalytic material
CN114870869A
Method for preparing polyvinylidene fluoride and titanium dioxide (PVDF / TiO2) compounded nanofiber membrane
CN102704190A
NiS / Cd1-xZnxS koelreuteria paniculata crystal nanorod composite photocatalyst as well as preparation method and application thereof
CN114618530A